Improvement of the performance of a hydrocracking reactor using a computational fluid dynamics perspective (2015)
The distribution of the liquid phase at the top of the catalytic bed of a hydrocracking trickle bed reactor was obtained by CFD simulations and coupled to a 1-D hydrocracking reactor model, used to evaluate the performance of the reactor. The design of the distribution system, that operated at industrial conditions (644K and 17MPa), was based on a multiphase CFD study carried out with the commercial software ANSYS Fluent v.15. Three CFD simulations were needed to accurately describe the distribution at the top of the reactor: (1) the gas phase entering to the vapor lift distributor (VLD) unit, a device used to mix the gas and the liquid phases; (2) the VLD itself, and (3) the dispersion zone where a mixture of both phases falls to the top of the catalyst bed from the outlet of the VLD unit. The CFD simulations and the 1-D hydrocracking reactor model were validated using literature data. A parameter variation process was done at the VLD unit and the dispersion zone, to improve the distribution of the liquid phase at the top of the catalytic bed and the performance of the hydrocracking reactor. For the VLD unit the parameter varied was the ratio between the separation plate height and the total VLD height. A comparison of three different cases showed that a value of 0.83 is the best configuration. The evaluation of two different depth distances for the dispersion zone indicates that 40cm offered the best liquid distribution at the top of the bed. With the configurations selected an analysis of different profiles at the top of the catalyst bed, showed the advantage of a careful description of the distribution in the top tray when predicting reactor conversion. An arrangement of VLD units allowed for a conversion of 0.1284 for conditions selected, which is comparable with obtained for the completely mixed case. These results indicate the importance of a proper description of the distribution system in this type of reactors.